A systematic review and comprehensive legislative framework to address chemical assault globally. Issue 9 (18th September 2020) - Kazerooni, Yasaman; Mishra, Brijesh; Gibran, Nicole; Adu, Emmanual; Clarke, Damian; Pham, Tam; Stewart, Barclay T
Abstract: The incidence of chemical assault is increasing globally. In response, a number of countries are proposing legislation. However, current legislative initiatives are uncoordinated and do not address the spectrum of activities to prevent and care for victims of chemical assaults. To fill this gap, we aimed to review legislation, policies and regulations relevant to chemical assault to classify and catalogue current strategies into a legislative framework. Terms related to chemical assault were used to systematically search the academic, lay and legal literatures. Chemical assault was defined as the use of acid or another caustic or corrosive substance or vitriol by one person against another with the intent to injure or disfigure. Reports that described the use of chemical weapons in warfare were excluded. A second search of national legislations of countries with reports of chemical assaults was performed to identify enacted laws and gaps in legislative approaches to chemical assault control. Data regarding relevant laws, policies and regulations were extracted. The findings were used to classify and catalogue current strategies into a legislative framework using content analysis. The search returned 3769 records. Chemical assaults were reported from 104 countries. Using legislation from those countries, a framework consisting of five legislative priorities was developed: (a) apply a public health approach; (b) adopt legal definitions specific to chemical assault; (c) control chemical supply, sales and procurement; (d) facilitate justice; and (e) support survivors. Although many countries have implemented one or more of these legislative priorities, no country has a comprehensive address to chemical assault control. Comparative policy analysis and assessments of the impacts of legislative efforts may further inform strategies to prevent, prosecute and mitigate the impact of chemical assaults. In the meantime, advocacy groups and governments might consider implementation and enforcement of one or more components of this legislative framework to control the growing epidemic of chemical assault.